Gestión administrativa y su incidencia en la facturación de la corporación nacional de electricidad Quevedo CNEL periodo 2011-2012, Propuesta alternativa. - Mueckay Basurto, Silvia María (2013)
This research work was carried out to assess the impact of the AdministrativeOperative in the turnover of the National Power Corporation Quevedo CNEL. Inaddition to the following objectives set for the research: Determine the operational process of reading take electricity consumption and itsinfluence on the sales of the securities to pay customers CNEL-Quevedo.Investigate operational control of CNEL-Quevedo to the meters and theirrelationship to the diversion of electricity. To determine the impact of therecruitment process CNEL electric power consumption of unregisteredusers.Knowing the types of fees that are special customers, residential and its impact on the turnover of CNEL-Quevedo. Ask an optimization to reduce power losses of residential customers and specialQuevedo Canton. The CNEL National Power Corporation was established in December 2008 withthe merger of the 10 utilities that historically maintained the lowest managementindicators, having as its main task the reverse these indicators in order to improvethe situation of the 10 companies. The completion of this research work is necessary because nowadays diversion of energy losses constitute a large share of overall company losses, point mainly affects the profitability of turnover, this is due in large part to customers bothcommercial and industrial special diverting electricity consumption paying not real, but a much smaller amount. Among the problems encountered were: Incorrect assignment electricity rates tospecial customers, residential, negative impact on revenue collected, practicepower detour, slow process of hiring power. It showed the following hypothesis: The administrative-operational mismanagement negative impact on sales of the securities to pay Quevedo CNEL customers. Where is presented as solution to design a strategic plan for the reduction and control of electrical energy losses for the National Power Corporation Quevedo.